The origins of the social contract’s idea and the Modern constructivism - Proleiev, Sergii; Shamrai, Victoria (Sententiae, 2004)
The authors of the article aim to show the ideological and historical origins of the idea of a social contract, as well as the fundamental difference between the modern version of the social contract and its historical predecessors. By distinguishing between the synodal and contractual principles of integration, the authors conclude that the social contract is not a purely modern political idea. The contractual principle as the basis of the organization and legitimization of power was systematically developed already in the XIII-XIV centuries, taking the form of a socio-political program in the theory of the cathedral governance of the church. In contrast to medieval concepts, the modern social contract is not a consequence of God’s established order, but the will of human individuals. Due to this determination of will, individuals limit their natural freedom for the sake of the possibility and good of common existence.